IDIOMS ON THE DIALECT OF WESTERN THRACE TURKS IN GREECE - Muharrem ÖZDEN (Zeitschrift für die Welt der Türken, 2017)
Idioms are stereotypes, are formed by using more than one word together to put into words a specific concept, emotion or situation. Idıoms give hints about lyrical ways of expression, history of the community, lifestyle, traditions and various features. The number of academic studies on the language and vocabulary of the Turkish community that living in the Greek territories and known as the Western Thrace Turks is very small. Serious academic field work done in this area will inform us about the region's rich vocabulary. In our study, the vocabulary sections of five different studies on this region were scanned and concentrated on the idioms in the region.